Preparados homeopáticos no manejo da lagarta-do-cartucho Spodoptera frugiperda (Lepidoptera: Noctuidae) e do percevejo barriga-verde Dichelops melacanthus (Hemiptera: Pentatomidae) na cultura do milho (Zea mays) - Modolon, Tatiani Alano (2013)
The current system of corn production, provide high productivity while favoring pest outbreaks, such as the stink bug Dicheplos melacanthus and fall armyworm Spodoptera frugiperda. Conventional control strategies have been ineffective so far. This study aimed to evaluate the impact of homeopathic preparations on the development of S. frugiperda and D. melacanthus in corn plants. To study the consumption of fall armyworm S. frugiperda seeds were treated before planting by soaking in distilled water and homeopathic preparations at a dose of 1 mL.L-1. After soaking, the seeds were sown in pots. In experiments with fall armyworm in addition to the seed treatment (a), the dynamizations 12, 36, 60 and 84CH (centesimal hahnemaniana) of Silicea were applied in spraying (b) or irrigation (c), with an first application was made just after emergence, the second in V2 stage, and the third application in V3 stage of corn plants. Leaf sections of plants at V6 stage derived from the respective treatment were provided daily to caterpillars in individualized test tubes and maintained in the development room at 25 ± 3 °C and 14 hours photoperiod. Were evaluated consumption of leaves, formation and sex ratio of pupae and adults, fertility, fecundity, longevity of adult and food preference in free choice test. For the experiment with green-belly stink bug, D. melacanthus, homeopathic preparations Nux vomica was also applied as seed treatment (a) the dynamizations 12, 36, 60 and 84DH (decimal order of Hering) and combined with spraying (b) or irrigation (c), and started ten days after sowing and followed within three days until the 22th day after sowing, totaling five applications. Five days after the last application, fresh and dry mass of shoots and roots, root volume, primary root length, height and stem diameter of corn plants were evaluated. On the sixth day after the last treatment, the plots replicas were subjected to stress by the insect. Corn plants were infested with a D. melacanthus bug for 36 hours. Ten days after removal of the bug, the classification of attacked plants was performed through a rating scale of damage. Data analysis showed that corn plants sprayed or irrigated with 36CH Silicea interfered in the consumption and utilization of food. In addition, it provided greater amount of pupae and adults of deformed S. frugiperda. Plants sprayed or irrigated on soil with 36CH Silicea also interfered with fertility and fecundity of S. frugiperda, providing shorter oviposition and post-reproductive periods, as well as fewer egg masses, eggs per ovoposition and eggs per female. The results suggest that larvae of S. frugiperda have difficulty while feeding on corn plants sprayed or irrigated with 36CH Silicea. Corn plants treated with 36CH Silicea homeopathic preparation, applied by spraying the shoots or by irrigating the soil, interfered with the feeding and, therefore, with fertility and fecundity of S. frugiperda, reducing insect population. The method of application of homeopathic preparations Nux vomica more suitable for the corn crop was in the through irrigation on soil. Nux vomica at 33, 36 and 38DH irrigated to soil favored the early development of shoots and roots of corn plants. Corn plants irrigated Nux vomica 36 and 38DH were not damaged by green-belly stink bug D. melacanthus, showing the effect of repellency or not food preference